An Assessment of The Knowledge, Risk Perception and Attitudes of Healthcare Workers in A Tertiary Health Facility in Southwest Nigeria to The Covid 19 Pandemic - Adeniyi, MA; Olajide, TG; Aderukuola, B; Popoola, GO; Olasehinde, KO; Adegbiji, WA (Journal of Public Health International, 2022)
Aim Covid 19 is a pandemic that has ravaged the world resulting in thousands of deaths. This study aims to assess the knowledge, risk perception, and attitude of health care workers (HCWs) to the pandemic. Methodology This was a hospital based descriptive cross sectional study conducted among health care workers who were staff of the hospital. Data collected includes socio demographic characteristics, data on knowledge, risk perception and attitude. Results A total of 288 HCWs participated in the study. Participants had good knowledge at 95.6%, major source of knowledge includes internet/social media 68.8%, radio 34.6% and television 28.3%. About 92.6% of the respondents also had positive attitude while 89.75 of the respondents had a positive risk perception. Conclusion Overall, there was a high level of knowledge, high positive attitude and a high risk perception in the study. Consequently, to ensure that this high level is maintained, there is need for continuous health education and promotion.
Keywords: Knowledge; risk perception; attitude; health care workers